Humeral shaft cerclage wiring: a safe technique to prevent radial nerve injury. (November 2017) - Grechenig, Stephan; Hohenberger, Gloria; Bakota, Bore; Staresinic, Mario; Grechenig, Peter; Ernstberger, Antonio
Abstract : Abstract: Humeral periprosthetic fractures are a challenging problem and their occurrence has increased, particularly over the last decade. The role of cerclage wires or cables in these fractures includes revisions with longer stems, and augmentation of a plate osteosynthesis in which the stem does not allow additional screw placement or structural bone grafts as supplementary fixation. These procedures are demanding because of the proximity of the radial nerve within the operating field. Placing a cerclage wire or cable around the fractured fragments offers a simple and safe procedure to avoid radial nerve injury or palsy in the treatment of complex humeral shaft fractures. This new technique is a simple and safe procedure to place a cerclage wire or cable around the humeral shaft.